Concurrent germline BRCA1, BRCA2, and CHEK2 pathogenic variants in hereditary breast cancer: a case series - Sukumar, Jasmine; Kassem, Mahmoud; Agnese, Doreen; Pilarski, Robert; Ramaswamy, Bhuvaneswari; Sweet, Kevin; Sardesai, Sagar (Breast Cancer Research and Treatment, 2021)
Concurrent germline (g) pathogenic variants related to hereditary breast cancer represent a rare occurrence. While double heterozygosity in gBRCA1 and gBRCA2 has been reported in the past, herein we describe the first case of three known concurrent pathogenic variants identified in a family with a strong history of breast cancer.